O impacto das condições de trabalho na atividade de equipes multiprofissionais de saúde - Valéria Maria da Conceição Mota (2019)
Teamwork is a management strategy frequently adopted by organizations in Brazil. In face of the challenges arising from the situation of instability experienced in organizational environment nowadays, from the studies on the nature and functioning of work teams, with a view to a more detailed understanding of their performance, the teams are necessary to make better use of their specificities. From the perspective of Psychosociology, the main objective of this research was to identify what proportion the work conditions affect team performance, in according to the perception of the health teams workers. We locate the teams among the health workers from the Potency evaluation. The sample consisted of 452 health professionals in public institutions of Minas Gerais municipalities. We also interviewed 14 of these workers. We applied on the multi-methodological perspective, that included Structural Equation Modeling techniques, categorical content analysis of interview content and free observations in the analysis of data. We identify the factors that better described of the working conditions by health professionals in the sample. The analyzes also revealed that Risks, Control, Contradictions and Violence – factors of working conditions – are variables that explain more the Potency of Teams. The thesis contributed with technical products – questionnaires with validity evidence presented – and knowledge about the health teams that they can indicate ways to amplify professionals’ well-being and the efficiency of health system.